Puberty- and Menstruation-Related Stressors Are Associated with Depression, Anxiety, and Reproductive Tract Infection Symptoms Among Adolescent Girls in Tanzania. - Cherenack, Emily M.; Sikkema, Kathleen J. (International Journal of Behavioral Medicine, 2022)
Background: Puberty and menstruation are significant stressors for adolescent girls and young women in low-resource settings in sub-Saharan Africa. However, little is known about the impact of these stressors on girls' mental health and reproductive health. Methods: In 2018, a cross-sectional self-report survey was conducted with 581 adolescent girls and young women between 13 to 21 years old who had reached menarche and were attending secondary school in Moshi, Tanzania. Structural equation modeling was used to examine the relationships of puberty-related stressors and menstruation-related stressors (menstrual deficits, movement/activity difficulties, and menstrual symptoms) to depression, anxiety, and the likelihood of reporting reproductive tract infection (RTI) symptoms. Results: Puberty-specific stressors, menstrual symptoms, and menstrual deficits were associated with depression and anxiety. Movement/activity difficulties were associated with anxiety. Increases in menstrual symptoms, menstrual deficits, puberty stressors, and depression were associated with an increased likelihood of reporting a lifetime RTI. However, the relationship of puberty stressors and depression with RTIs was no longer significant in two of three models after correcting for Type I error. Conclusions: Overall, puberty- and menstruation-related stressors were associated with mental health and symptoms of reproductive tract infections. This suggests there is an important relationship between stressors specific to adolescent girls and young women during puberty, mental health, and reproductive health. There is a need for adolescent-tailored interventions to reduce the negative impact of stressors among girls transitioning through puberty in sub-Saharan Africa.